The value of communication in resource allocation decisions* - BALAKRISHNAN, RAMJI (Contemporary Accounting Research, 1992)
This article examines the value of communication in a setting in which the owner and the manager of a firm differentially share the costs and benefits of information acquisition. Absent communication, the optimal contract induces allocative distortions to enhance the information content (about whether the manager expended effort in searching for additional information pertinent to the allocation decision) of the observed output. Communication has value because it reduces the value of the information externality in the observed output and, thus, reduces allocative distortions. Hence, the results lend support to the use of accounting reports (e.g., budgets) and ex post monitoring of decisions (e.g., an internal audit) in managerial performance evaluation. However, unless the manager's search is observable, it is optimal to use the information in the observed outcomes in compensating the manager. This finding highlights that the optimality of observed resource allocation practices cannot be evaluated independently of the larger problem of motivating the manager to acquire pertinent information because the information acquisition and resource allocation problems cannot be decomposed. Résumé. L'auteur examine la valeur de la communication dans un environnement dans lequel le propriétaire et le gestionnaire d'une entreprise partagent de façon différente les coûts et les avantages de l'acquisition d'information. Si la communication est inexistante, le contrat optimal induira des distorsions dans l'affectation des ressources visant à augmenter le contenu en information (relativement à l'ampleur des efforts déployés par le gestionnaire pour obtenir de l'information supplémentaire pertinente à la décision d'affectation) des résultats observés. La valeur de la communication réside dans le fait qu'elle réduit celle de l'extériorité de l'information dans les résultats observés et, par conséquent, diminue les distorsions dans l'affectation des ressources. Les résultats viennent donc appuyer l'utilisation des rapports comptables (les budgets, par exemple) et du contrôle a posteriori des décisions (la vérification interne, par exemple) dans l'evaluation du rendement du gestionnaire. Toutefois, à moins que la recherche d'information par le gestionnaire ne soil observable, il est optimal d'utiliser l'information contenue dans les résultats observés pour décider de la rémunération du gestionnaire. Cette conclusion met en relief le fait que le caractère optimal des méthodes observées d'affectation des ressources ne peut être évalué isolément du problème plus large de la motivation du gestionnaire à faire l'acquisition de l'information pertinente, les problèmes d'acquisition d'information et d'affectation des ressources étant indissociables.